Video-Based Self-Assessment as an Alternative Speaking Assessment Method for High School English Language Learners. - To'raboyeva Xumora; Mukhabbat Anatolevna Yusupova (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
In the context of English language education for high school students who are English Language Learners (ELLs), traditional speaking assessments often face challenges such as subjectivity, anxiety induction, and limited opportunities for self-reflection. This study explores video-based self-assessment as a viable alternative method to enhance speaking skills, promote learner autonomy, and reduce evaluation biases. Drawing from empirical research and pedagogical theories, the investigation examines how video recordings enable students to analyze their own oral performances, identify strengths and weaknesses in pronunciation, fluency, vocabulary, and non-verbal cues, and set personal improvement goals. Through a mixed-methods approach involving high school ELLs in Uzbekistan and comparative international cases, the results indicate significant improvements in speaking confidence and proficiency, with mean scores rising by approximately 10-15% after iterative self-assessments [1, p. 98-101]. Student feedback highlights reduced anxiety and increased motivation, while challenges like technical access and time constraints are addressed. This method aligns with communicative language teaching principles and supports inclusive education in multilingual settings, particularly in Uzbekistan where English teaching emphasizes competency-based outcomes [5, p. 10-15]. Ultimately, video-based self-assessment emerges as a cost-effective, student-centered tool that fosters reflective learning and better prepares ELLs for real-world communication.